2020
DOI: 10.1111/2041-210x.13518
|View full text |Cite
|
Sign up to set email alerts
|

Defining and evaluating predictions of joint species distribution models

Abstract: Joint species distribution models (JSDMs) simultaneously model the distributions of multiple species, while accounting for residual co‐occurrence patterns. Despite increasing adoption of JSDMs in the literature, the question of how to define and evaluate JSDM predictions has only begun to be explored. We define four different JSDM prediction types that correspond to different aspects of species distribution and community assemblage processes. Marginal predictions are environment‐only predictions akin to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 41 publications
(66 reference statements)
0
81
0
Order By: Relevance
“…It is possible that more realistic and complex mechanisms driving these processes will weaken associations between pattern and process or create biases in the partitioning of the variation revealed by JSDMs. However, the developments of JSDMs are still progressing, and we anticipate that future developments will solve some of these problems (see Wilkinson et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that more realistic and complex mechanisms driving these processes will weaken associations between pattern and process or create biases in the partitioning of the variation revealed by JSDMs. However, the developments of JSDMs are still progressing, and we anticipate that future developments will solve some of these problems (see Wilkinson et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent studies have suggested that J-SDM do not improve species assemblage predictions 21,52 , in fact, richness predictions from S-SDMs and J-SDMs tend to return similar outcomes 52 , but see 53 . Although J-SDM represent an outstanding alternative for modeling and predicting biodiversity at assemblage level 50,53 , this kind of biodiversity models become untraceable when they are applied to large datasets 52,54 (e.g., NEON or FIA datasets), in other words, the species-pairwise dependencies matrix or residual correlation matrix increases quadratically by adding new species to the dataset 54 . Further research is needed to correctly predict biodiversity at the assemblage level.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, we acknowledge that we evaluated only one type of biodiversity model-S-SDM using two stacking procedures-and that other biodiversity models such as the Joint-SDM (J-SDM) 49,50 , could potentially improve biodiversity predictions by jointly estimating both the species-environment relationships (as in SDMs) and the species-pairwise dependencies-that re ect patterns of co-occurrence -not accounted by the covariates [50][51][52] . Nevertheless, recent studies have suggested that J-SDM do not improve species assemblage predictions 21,52 , in fact, richness predictions from S-SDMs and J-SDMs tend to return similar outcomes 52 , but see 53 . Although J-SDM represent an outstanding alternative for modeling and predicting biodiversity at assemblage level 50,53 , this kind of biodiversity models become untraceable when they are applied to large datasets 52,54 (e.g., NEON or FIA datasets), in other words, the species-pairwise dependencies matrix or residual correlation matrix increases quadratically by adding new species to the dataset 54 .…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, recent studies have suggested that J-SDM do not improve species assemblage predictions 21 , 53 , in fact, richness predictions from S-SDMs and J-SDMs tend to return similar outcomes 53 , but see Ref. 54 . Although J-SDM represent an outstanding alternative for modeling and predicting biodiversity at assemblage level 51 , 54 , this kind of biodiversity models become untraceable when they are applied to large datasets 53 , 55 (e.g., NEON or FIA datasets), in other words, the species-pairwise dependencies matrix or residual correlation matrix increases quadratically by adding new species to the dataset 55 .…”
Section: Discussionmentioning
confidence: 99%
“… 54 . Although J-SDM represent an outstanding alternative for modeling and predicting biodiversity at assemblage level 51 , 54 , this kind of biodiversity models become untraceable when they are applied to large datasets 53 , 55 (e.g., NEON or FIA datasets), in other words, the species-pairwise dependencies matrix or residual correlation matrix increases quadratically by adding new species to the dataset 55 . Further research is needed to correctly predict biodiversity at the assemblage level.…”
Section: Discussionmentioning
confidence: 99%